2019
DOI: 10.1063/1.5120429
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical systems approach to study thermoacoustic transitions in a liquid rocket combustor

Abstract: Liquid rockets are prone to large amplitude oscillations, commonly referred to as thermoacoustic instability. This phenomenon causes unavoidable developmental setbacks and poses a stern challenge to accomplish the mission objectives. Thermoacoustic instability arises due to the nonlinear interaction between the acoustic and the reactive flow subsystems in the combustion chamber. In this paper, we adopt tools from dynamical systems and complex systems theory to understand the dynamical transitions from a state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The different operating conditions of a thermoacoustic combustor have been extensively studied in the literature both in laboratory conditions and model system data [67]. Measures based both on RPs and recurrence networks have been successfully applied to detect dynamical transitions between different regimes [11,70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different operating conditions of a thermoacoustic combustor have been extensively studied in the literature both in laboratory conditions and model system data [67]. Measures based both on RPs and recurrence networks have been successfully applied to detect dynamical transitions between different regimes [11,70].…”
Section: Resultsmentioning
confidence: 99%
“…Positive feedbacks between both may lead into a state called thermoacoustic instability, enhancing heat transfer to the walls of the combustion chamber and resulting in increased mechanical stress. This can cause severe damages to an aircraft's engine or shutdown in the case of a power plant [67]. The parameter which can drive the turbulent system into an unstable state is the fuel/air ratio.…”
Section: Application To Thermoacoustic Instability Time Seriesmentioning
confidence: 99%
“…Kasthuri et al [93] showed several measures based on multifractal theory and recurrence quantification analysis. They find that these are robust measures in distinguishing dynamical states occurring in a model rocket engine combustor.…”
Section: Recurrence Quantification Analysismentioning
confidence: 99%
“…The design maintains similarities with several other rocket and gas turbine combustion experiments studied at Purdue University. 35,[37][38][39][40] VIPER-M was designed to promote self-excited, transverse instabilities while operating at a mean chamber pressure up to 825 kPa with an inlet air temperature up to 510 K. The multi-element configuration supports jet-stabilized combustion with flames anchored at the injector-exit plane (y ¼ 0), as labeled in Figure 1. This injector configuration is similar to the FLOX V R combustion experiments, which have been widely studied.…”
Section: Combustor Designmentioning
confidence: 99%